HUBUNGAN SUMBER INFORMASI DENGAN PENGETAHUAN TENTANG TABLET FE PADA REMAJA DI DESA SEWAN KLATEN - Atik Mahmudah Aji Pamungkas; Kuswati; Diana Sari Setiyaningtyas (Rena Cipta Mandiri, 2025)
Anemia among adolescent girls (Rematri) in Indonesia remains a significant health issue, with a prevalence of 48.9% according to Riskesdas 2018. This issue is particularly prominent in the age groups of 15-24 years and 25-34 years. Anemia can be managed through the consumption of iron supplementation tablets (TTD) or Fe tablets, but the coverage of Fe tablet distribution in Central Java remains low at 29.3%, much lower than in Bali, which reaches 95.1%. Knowledge about Fe tablets is crucial for adolescents to understand their role in preventing anemia and improving hemoglobin levels. This study aims to determine the relationship between information sources and the knowledge of adolescent girls about Fe tablets in Sewan Village, Kedungampel, Klaten. The research method used is quantitative with a cross-sectional design, involving 49 adolescent girls aged 13-19 years who have reached menarche. A questionnaire was used as the instrument, and data were analyzed using the Chi-square test. The results showed an Asymp. Sig value of 0.025, indicating no significant relationship between information sources and knowledge about Fe tablets among adolescent girls in Sewan Village, Klaten.